2021
DOI: 10.22207/jpam.15.4.62
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Characterization of Antimicrobial Agents Produced by Marine Aspergillus terreus She05 against Aeromonas hydrophila and other Applications

Abstract: Seven morphologically distinct marine fungi were isolated from sediment and Seawater samples at different sites along Alexandria seashore. Antagonism effect against Aeromonas hydrophila on purpose and other pathogen was estimated. The most promising isolate giving the highest antibacterial activity (14 mm) against A. hydrophila was morphologically and genetically identified as Aspergillus terreus SHE05 and the corresponding sequence was recorded in the GenBank database with accession no. MW772239. Time course … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The results of the GC-MS analysis showed that the major components in the petroleum extract were dodecanamine,N, N-dimethyl, lupeol, kojic acid and amyrin. Similarly, Abd El-Latif et al (2021) reported that in the GC-MS analysis, the predominant component of the ethyl acetate extract ingredients of A. terreus SHE05 isolated from Alexandria was the dodecanamine, N, N-dimethyl with the formula C 14 H 31 N. In addition, this substance possessed antibacterial properties and was previously produced by Many fungi including Citrullus colocynthis (Idan et al, 2015). Moreover, according to Li & Xiao https://mail.google.com/mail/u/3/#inbox/QgrcJHsNjpknSjsSRPMRRHRJvsdkXGjKScb?projector=1 1/1 (2018), lupeol derivatives exhibited anticancer activity against HepG2 cells, which explains our petroleum ether extract's activity against HepG2 and PC-3 cells.…”
Section: Discussionmentioning
confidence: 98%
“…The results of the GC-MS analysis showed that the major components in the petroleum extract were dodecanamine,N, N-dimethyl, lupeol, kojic acid and amyrin. Similarly, Abd El-Latif et al (2021) reported that in the GC-MS analysis, the predominant component of the ethyl acetate extract ingredients of A. terreus SHE05 isolated from Alexandria was the dodecanamine, N, N-dimethyl with the formula C 14 H 31 N. In addition, this substance possessed antibacterial properties and was previously produced by Many fungi including Citrullus colocynthis (Idan et al, 2015). Moreover, according to Li & Xiao https://mail.google.com/mail/u/3/#inbox/QgrcJHsNjpknSjsSRPMRRHRJvsdkXGjKScb?projector=1 1/1 (2018), lupeol derivatives exhibited anticancer activity against HepG2 cells, which explains our petroleum ether extract's activity against HepG2 and PC-3 cells.…”
Section: Discussionmentioning
confidence: 98%
“…These findings align with prior research, wherein the marine fungus Nodulisporium sp. KT29 was shown to enhance inhibition zones ranging from 9.3 to 13 mm [20].…”
Section: Resultsmentioning
confidence: 98%